2002
DOI: 10.1152/ajplung.00151.2002
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1stimulates HO-1 via the p38 mitogen-activated protein kinase in A549 pulmonary epithelial cells

Abstract: . TGF-␤1 stimulates HO-1 via the p38 mitogen-activated protein kinase in A549 pulmonary epithelial cells. Am

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 47 publications
1
68
2
Order By: Relevance
“…The rapid induction of HO-1 mRNA also distinguishes our findings from those of other reports in the literature. Interestingly, one notable exception was the rapid response to TGF-β reported by Ning et al in pulmonary epithelial cells [34]. In this study, HO-1 mRNA increased at 1 h and protein at 3 h postincubation.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The rapid induction of HO-1 mRNA also distinguishes our findings from those of other reports in the literature. Interestingly, one notable exception was the rapid response to TGF-β reported by Ning et al in pulmonary epithelial cells [34]. In this study, HO-1 mRNA increased at 1 h and protein at 3 h postincubation.…”
Section: Discussioncontrasting
confidence: 67%
“…Seminal studies support a role for these kinases as mediators of HO-1 induction in a broad range of tissues and cell types. Studies have shown that HO-1 is induced via the ERK pathway by LPS + IFN-γ [32], through p38 MAPK in murine macrophages in response to IL-1β, and in human lung epithelial cells by 34]. However, care must be taken not to generalize, as the signaling pathways that are activated are both agonist-and species-specific.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…TGF β1 is known to induce HO-1 expression in pulmonary epithelial cells (Ning et al 2002), human renal proximal tubule cells (Hill-Kapturczak et al 2000), and also in WI-38 HDFs (Pascal et al 2007). HO-1 expression is transcriptionally activated by agents that generate reactive oxygen species (Soares and Bach 2009), and it has been already shown to be overexpressed in prematurely senescent WI-38 HDFs after exposure to t-BHP and ethanol (Pascal et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Total protein of fibroblast was prepared and Western blotting was performed by using rabbit anti-Egr-1 antibody as described (18). Nuclear protein was prepared and Egr1 DNA-binding activity was measured by a BD Mercury TransFactor kit according to the manufacturer's instructions (BD Biosciences, Palo Alto, CA).…”
Section: Preparation and Treatment Of Cigarette Smoke Extract (Cse)mentioning
confidence: 99%